Hopane and lupane triterpenes from leaves and stem bark of Aegle marmelos (Rutaceae) - Ahmad, S.; Riyanto, Sugeng; Sukari, Mohd Aspollah; Rahmani, Mawardi; Ali, Abdul Manaf (Chemic Publishing Company, 2013)
Two hopane and two lupane triterpenes have been isolated from leaves and stem bark of Aegle marmelos originated from Yogyakarta, Indonesia. Hopane triterpenes identified as 6a,22-dihydroxyhopane (1) and 15a,22-dihydroxyhopane (2) were isolated from petroleum ether extract of the leaves, while lupane triterpenes; 20(29)-lupene-3a-ol (3) and 20(29)-lupene-3-on (4) were isolated from the stem bark. The structure of the compounds were elucidated using spectroscopic methods and by comparison with previous data.